2021
DOI: 10.1007/s40368-021-00641-2
|View full text |Cite
|
Sign up to set email alerts
|

Root canal instrumentation efficacy of non-fused and fused primary molar roots: a micro-computed tomography study

Abstract: Root canal instrumentation efficacy of non-fused and fused primary molar roots: a micro-computed tomography study. European archives of paediatric dentistry, 1-17.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
(82 reference statements)
0
3
1
Order By: Relevance
“…Compared with the results of our study in terms of the evaluated parameters, there are a few studies, which evaluated the efficacy of manual and rotary instrumentation in primary molar teeth. 34,35 In contrast to the present findings, Esenturk et al 34 compared rotary instrumentation systems (OneShape and Revo-S) and K-files and demonstrated that most of the root canal walls remained untouched (76.5%) irrespective of the preparation system used. Whereas one rotary system (Revo-S) showed better results than hand K-files, the other (OneShape) had a similar untouched surface area when compared to hand K-files.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…Compared with the results of our study in terms of the evaluated parameters, there are a few studies, which evaluated the efficacy of manual and rotary instrumentation in primary molar teeth. 34,35 In contrast to the present findings, Esenturk et al 34 compared rotary instrumentation systems (OneShape and Revo-S) and K-files and demonstrated that most of the root canal walls remained untouched (76.5%) irrespective of the preparation system used. Whereas one rotary system (Revo-S) showed better results than hand K-files, the other (OneShape) had a similar untouched surface area when compared to hand K-files.…”
Section: Discussioncontrasting
confidence: 88%
“…Whereas one rotary system (Revo‐S) showed better results than hand K‐files, the other (OneShape) had a similar untouched surface area when compared to hand K‐files. Dalzell et al 35 reported that the untouched canal surface areas in both nonfused and fused primary teeth were 62% and 69.2% with Mtwo, Reciproc Blue, and K‐files root canal preparation without differences between the root canal preparation protocols. These contradictory results may be explained by differences in method, preparation technique, and sample selection.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the simulated root canals allowed direct visual comparison of the shaping ability of the tested Ni-Ti instruments. In recent years, micro-computed tomographic (M-CBCT) three-dimensional analysis has been used in some studies to evaluate the shaping effects of the instruments [15][16][17][18]. Considering M-CBCT's high cost, extensive data, and complicated analysis, the present study used the classic method of superimposition of two-dimensional images to give comparable results for the evaluation of shaping effects of the instruments in S-shaped simulated canals.…”
Section: Selection Of Sample and Evaluative Methodsmentioning
confidence: 99%
“…The roots that fuse also determine the fusion type and are used by several studies categorizing fusion morphology into 6–7 distinct types (Martins et al, 2016; Zhang et al, 2017). In the Zhang et al modification of Yang et al classification (Yang et al, 1988), the number of fused roots increases from type 1 to 6, which has a single conical root (Dalzell et al, 2021). The frequency of different fusion types seems to vary according to the ethnicity of the patients, sample size, and the evaluation method, as the fusion of buccal roots (Type 1) is the most frequently reported fusion type over all the studies (Aydin, 2021; Kim et al, 2012; Martins et al, 2016; Ordinola‐Zapata et al, 2017).…”
Section: Introductionmentioning
confidence: 99%